The importance of data analysis in business - Nur Sa’adatul Afzan, Jusoh (2019)
Having the means for data analysis in a business can increase the value and profit of a company in the future. In fact, in the present digital era, security aspect and digital innovation have become essential features for an organisation to compete in a healthy way. According to Malaysia Airlines Berhad (MAS) Business Intelligent Insights data analyst Parjit Singh Ranjeet Singh, data analysis could also be used for human resource development such as in terms of division of work and matching the task according to skills of the staff.